Gender bias in cardiovascular healthcare of a tertiary care centre of North India. Issue 1 (25th May 2016) - Chhabra, Shibba Takkar; Masson, Sarbjit; Kaur, Tripat; Gupta, Rajiv; Sharma, Sarit; Goyal, Abishek; Singh, Bhupinder; Tandon, Rohit; Aslam, Naved; Mohan, Bishav; Wander, Gurpreet Singh
Abstract : Objectives: To analyse the gender bias in paediatric patients referred for free cardiac treatment as part of School Health Programme at a tertiary care centre in North India. Methods: A total of 537 children were referred for further management of congenital heart disease or rheumatic heart disease. Of these, 519 underwent cardiac intervention, and the data from their records were analysed retrospectively to determine any gender disparity in the utilisation of cardiac surgery. Results: Of the 519 children studied, only 195 (37.6%) were girls, while the remaining 324 (62.4%) were boys (male-to-female ratio of 1.66:1, p<0.0001), indicating a large gender divide. Gender bias was found to be prevalent across all the age groups irrespective of the type of cardiac ailment. Moreover, no statistically significant difference was found between the urban and rural populations (male-to-female ratio of 1.64:1 in rural and 1.71:1 in urban populations; p=0.823) in terms of gender disparity. Conclusions: Significant gender discrepancies exist in healthcare-seeking behaviour of patients in North India despite the provision of free cardiac treatment. An equal prevalence of gender bias in urban and rural communities points towards deep-rooted social norms beyond just the economic constraints. Healthcare policies ensuring equal treatment of male and female children should be promulgated to ensure a complete eradication of this social evil.